1996
DOI: 10.1111/j.1476-5381.1996.tb15282.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of putative 5‐ht7 receptors mediating direct relaxation in Cynomolgus monkey isolated jugular vein

Abstract: 1 5-Hydroxytryptamine (5-HT) receptors mediating contraction and relaxation are present in Cynomolgus monkey isolated jugular vein denuded of endothelium. 2 In the absence of spasmogen, a-methyl-5-HT and sumatriptan contracted the tissues with potency values (pEC50) of 6.8 (n = 2) and 6.4 + 0.1 (mean + s.e. mean, n = 3), respectively. In contrast, 5-HT caused an initial contraction (10 nM -1 pM), followed by relaxation (1 pMM-32 yM). The contractile effect of x-methyl-5-HT was antagonized by ketanserin with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 12 publications
7
59
0
Order By: Relevance
“…This explanation is, however, unlikely in our preparation as we have shown that fetal and 0 ± 24 h rabbit PRAs relax to acetylcholine . 5-HT receptors are known to mediate vasodilation in blood vessels either directly via 5-HT receptors located on the vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996) or indirectly via endothelial released NO (Bodelson et al, 1993;Glusa & Richter, 1993;Glusa & Roos, 1996). We show that, in 4-and 7-day-old rabbit small pulmonary arteries, 5-CT-evoked vasodilation is inhibited by the NO synthase inhibitor L-NAME.…”
Section: -Ht Receptor-induced Vasodilationmentioning
confidence: 70%
See 3 more Smart Citations
“…This explanation is, however, unlikely in our preparation as we have shown that fetal and 0 ± 24 h rabbit PRAs relax to acetylcholine . 5-HT receptors are known to mediate vasodilation in blood vessels either directly via 5-HT receptors located on the vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996) or indirectly via endothelial released NO (Bodelson et al, 1993;Glusa & Richter, 1993;Glusa & Roos, 1996). We show that, in 4-and 7-day-old rabbit small pulmonary arteries, 5-CT-evoked vasodilation is inhibited by the NO synthase inhibitor L-NAME.…”
Section: -Ht Receptor-induced Vasodilationmentioning
confidence: 70%
“…In other vascular beds, 5-HT can induce endothelium-dependent vasodilation via the 5-HT 2C receptor (Bodelson et al, 1993), the 5-HT 2B receptor (Glusa & Roos, 1996;Ellis et al, 1995) and the 5-HT 1D/1B receptor (Gupta, 1992). There is also evidence that 5-HT can mediate vasodilation directly through 5-HT 4 and 5-HT 7 receptors located on vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996;Terron, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the periphery, the 5-HT7 receptor is expressed in vascular smooth muscle (Ullmer et al, 1995), where activation probably causes relaxation in vitro (Sumner et a!., 1989;Cushing et a!., 1996;Leung et a!., 1996;Villalón et a!., 1997) and the prolonged hypotension following intravenous 5-HT in vivo (De Vries et a!., 1997). Within the CNS, 5-HT7 receptor-mediated effects are less well defined .…”
mentioning
confidence: 99%